Do you want to be my friend? - Carle, Eric. (New York : Scholastic Inc., 1971)
A mouse searches everywhere for a friend.
G1
Keywords: Mice -- Juvenile fiction; Animals -- Juvenile fiction; Mice -- Fiction; Animals -- Fiction; Stories without words